Venular-centered thrombo-inflammation drives microvascular failure after arterial recanalization in acute mesenteric ischemia - Déborah François; Lambert Kernanet; Melinda Bajul; Abigail Brami; Véronique Arocas; Marie-Christine Bouton; Dominique Cazals-Hatem; Kevin Guedj; Benoit Ho-Tin-Noé; Olivier Corcos; Yacine Boulaftali; Alexandre Nuzzo (Communications Medicine, 2026)
Abstract Background Acute mesenteric ischemia (AMI) remains associated with high mortality despite prompt revascularization, suggesting that downstream ischemia–reperfusion injury contributes to poor outcomes. However, the microvascular mechanisms underlying this process are not entirely defined. Methods We analyzed admission blood samples from patients with arterial AMI and non-ischemic controls enrolled in the SURVIBIO diagnostic study (NCT03518099). We also investigated thrombo-inflammatory responses in a murine superior mesenteric artery occlusion (SMAO) model. In mice, intravital microscopy was used to directly visualize mesenteric microcirculatory flow and thrombo-inflammatory events during ischemia–reperfusion. Results Patients with AMI display a marked systemic thrombo-inflammatory profile, characterized by elevated inflammatory markers, neutrophil activation, platelet activation, and alterations in coagulation-related proteins, which are closely mirrored in the SMAO model. Intravital microscopy reveals a dissociation between arterial and microvascular reperfusion: while arteriolar flow partially recovers after recanalization, venular perfusion remains severely impaired and is associated with early blood cell stasis and stable venular thrombus formation. Thrombi develop through a sequential process initiated during ischemia and amplified during reperfusion. Conclusion Together, these findings suggest that venular-centered thrombo-inflammation is closely associated with microvascular dysfunction and intestinal injury in arterial AMI. This work provides a framework for targeting thrombo-inflammatory pathways beyond arterial reperfusion that may extend to other clinical forms of AMI, including non-occlusive mesenteric ischemia (NOMI).